Mediating Roles of Anxiety, Self-Efficacy, and Sleep Quality on the Relationship Between Patient-Reported Physician Empathy and Inflammatory Markers in Ulcerative Colitis Patients - Chen, Xiangfan (Med Sci Monit, 2019)
BACKGROUND: Empathy between doctor and patient has an important bearing on patient health. The purpose of this study was to assess whether anxiety, sleep quality, and self-efficacy of patients have mediating effects in the relationship of patient-reported physician empathy and inflammatory factor in ulcerative colitis (UC) patients. MATERIAL/METHODS: This study included 242 patients attended by 45 doctors. Self-reported doctors’ empathy ability was measured at patient admission (T1), and patient-reported physician empathy was measured 3 months later (T2). Patient anxiety, general self-efficacy, sleep, and inflammatory factor (IL-6) were measured on T1 and T2. Pearson correlation analysis was used to assess the relationships between self-reported doctor empathy ability and patient indices on T1 and T2. The relationships between anxiety, sleep quality, self-efficacy, IL-6, and patient-reported physician empathy were measured by Pearson correlation analysis and structural equation modeling. RESULTS: On T1, no significant correlation was reported between self-reported doctors’ empathy ability and indices of the patients (P>0.05). On T2, self-reported doctors’ empathy ability was significantly positively correlated with patient sleep and self-efficacy (P<0.01), and significantly negatively correlated with patient anxiety and IL-6 (P<0.01). Moreover, on T2, patient-reported physician empathy was negatively correlated with anxiety and IL-6 and was positively correlated with self-efficacy and sleep quality. The effect of patient-reported physician empathy on IL-6 was mediated by anxiety, sleep quality, and self-efficacy. CONCLUSIONS: The anxiety, self-efficacy, and sleep quality of UC patients had mediating effects in the relationship between patient-reported physician empathy and IL-6.